GAS-STING: a classical DNA recognition pathways to tumor therapy - Wang, Xinrui; Lin, Meijia; Zhu, Liping; Ye, Zhoujie (Frontiers in Immunology, 2023)
Cyclic GMP-AMP synthetase (cGAS), recognized as the primary DNA sensor within cells, possesses the capability to identify foreign DNA molecules along with free DNA fragments. This identification process facilitates the production of type I IFNs through the activator of the interferon gene (STING) which induces the phosphorylation of downstream transcription factors. This action characterizes the most archetypal biological functionality of the cGAS-STING pathway. When treated with anti-tumor agents, cells experience DNA damage that triggers activation of the cGAS-STING pathway, culminating in the expression of type I IFNs and associated downstream interferon-stimulated genes. cGAS-STING is one of the important innate immune pathways,the role of type I IFNs in the articulation between innate immunity and T-cell antitumour immunity.type I IFNs promote the recruitment and activation of inflammatory cells (including NK cells) at the tumor site.Type I IFNs also can promote the activation and maturation of dendritic cel(DC), improve the antigen presentation of CD4+T lymphocytes, and enhance the cross-presentation of CD8+T lymphocytes to upregulating anti-tumor responses. This review discussed the cGAS-STING signaling and its mechanism and biological function in traditional tumor therapy and immunotherapy.